The virtual forum as an alternative way to enhance foreign language learning (2008)
A web-based story sharing forum has been established to provide students in Bogotá, Colombia, New Brunswick, Canada and Dundee, Scotland with the opportunity to exchange cross-cultural stories as a complement to the regular ELT Curriculum. This paper will describe the process through which the exchange experience was established and the progress achieved by the group of Colombian students in their regular interaction through blogs, theme-based wikis, social forums and online debates. The teaching practices utilized in the forum have fostered the creation of communities of interest and practice among teachers and students in the forum. Early results suggest that this innovative way of implementing the ELT curriculum has promoted student involvement and language development through the use of ICTs. Key words: EFL learning mediated by ICTs, learning communities, blogs as tools for language learning El propósito de este artículo es compartir las experiencias de intercambio lingüístico y cultural que a través de un foro virtual (www.ourdigitalculture.net) se realizaron entre un grupo de estudiantes colombianos aprendiendo inglés como lengua extranjera y un grupo de estudiantes de New Brunswick, Canadá y Escocia a través de interacción regular con el uso de blogs, wikis, foros sociales y debates. El objetivo es mostrar el proceso de intercambio y los beneficios en el aprendizaje del grupo de estudiantes Colombianos. Las prácticas de enseñanza utilizadas en el foro han promovido la creación de comunidades de interés y comunidades de práctica entre los profesores y los estudiantes del foro. Los resultados preliminares sugieren que esta forma alternativa de implementar el currículo de inglés como lengua extranjera ha fomentado la participación activa de los estudiantes y el desarrollo de lengua extranjera mediante el uso de las TICs. Palabras clave: Aprendizaje de inglés como lengua extranjera mediado por las TICs, comunidades de aprendizaje, blogs como herramientas para el aprendizaje de lengua